2009
DOI: 10.1089/cpb.2008.0163
|View full text |Cite
|
Sign up to set email alerts
|

Can Blogging Enhance Subjective Well-Being Through Self-Disclosure?

Abstract: Based on the self-disclosure theory and the social capital theory, this study investigates if bloggers' self-disclosure enhances their social capital and if these capitals in turn enhance perception of subjective well-being (SWB). The results reveal that the self-disclosure of bloggers significantly and directly affects a blogger's perception of social integration, bonding social capital, and bridge social capital, which in turn promote bloggers' SWB. It appears that as bloggers share their inner thoughts of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 12 publications
4
83
1
1
Order By: Relevance
“…Blogging, though, is more than expressive writing; it is a social process (Pennebaker & Chung, 2011). Studies have shown that self-disclosure through blogging can increase perceived social support (Baker & Moore, 2008) and subjective wellbeing (Ko & Kuo, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Blogging, though, is more than expressive writing; it is a social process (Pennebaker & Chung, 2011). Studies have shown that self-disclosure through blogging can increase perceived social support (Baker & Moore, 2008) and subjective wellbeing (Ko & Kuo, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Internet-based self-help interventions further enhance self-disclosure through the disinhibiting effect of the Internet, leading users to offer more honest and accurate selfportrayals even in respect of sensitive topics (Fullwood, Sheenhan, & Nicholls, 2009;Tourangeau, 2004). Written self-disclosures of thoughts and feelings expressed online have been linked to improved social support, interpersonal communication and overall quality of life, allowing individuals to reflect on and communicate topics that are difficult to express in person (Gumbrecht, 2004;Ko & Kuo, 2009). Use of Internet-based self-help and peer-support groups resulted in increased professional help-seeking behaviour in one study of an online Gamblers Anonymous service (Cooper, 2004).…”
Section: Privacy and Anonymitymentioning
confidence: 99%
“…They exist independently from other interaction and communication, and therefore the user decides before producing and uploading his/her video what content he/she wants to disclose and whether to upload or not. This is also the case in other similar settings as weblogs (blogs), often characterized by voluntary self-disclosure (Bortree, 2005;Lee, Im & Taylor, 2008;Viegas, 2005;Ko & Kuo, 2009) as well as personal homepages (Misoch, 2007;Stern, 2002) or other self-related media products online (Misoch, 2013;Misoch, 2014). These communicational situations are characterized through asynchronicity and unidirectionality, and it seems that those factors might enhance self-disclosure: 'some people may even experience asynchronous communication as "running away" after posting a message that is personal, emotional, or hostile' (Suler, 2004).…”
Section: Characteristics Related To the Medium And/ormentioning
confidence: 78%
“…Seeking for contact: studies concerning blogs revealed that central motives for blogging are purposes of self-presentation, to express one's feelings (e.g., depression), and to find social contact. One study about blogs showed that the more information the blogger disclosed, the more social capital (Bourdieu, 2002) he/she gained (Ko & Kuo, 2009). If we transfer these findings to card stories on YouTube, these confessional videos could have the same goal.…”
mentioning
confidence: 99%